2020
DOI: 10.1002/stem.3159
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular osteoprogenitors are associated with transcortical channels of long bones

Abstract: Bone remodeling and regeneration are dependent on resident stem/progenitor cells with the ability to replenish mature osteoblasts and repair the skeleton.Using lineage tracing approaches, we identified a population of Dmp1+ cells that reside within cortical bone and are distinct from osteocytes. Our aims were to characterize this stromal population of transcortical perivascular cells (TPCs) in their resident niche and evaluate their osteogenic potential. To distinguish this population from osteoblasts/osteocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Dmp1 + perivascular cells can migrate out of the transcortical channel and expand and differentiate into osteoblasts in bone organ cultures. ( 91 )…”
Section: Diverse Origins Of Osteoblasts In Adult Bonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dmp1 + perivascular cells can migrate out of the transcortical channel and expand and differentiate into osteoblasts in bone organ cultures. ( 91 )…”
Section: Diverse Origins Of Osteoblasts In Adult Bonesmentioning
confidence: 99%
“…( 103,104 ) These observations were confirmed by a lineage‐tracing study using Dmp1‐creER , which can label the descendants of mature osteoblasts after a long chase, including bone‐lining cells and osteocytes. ( 105 ) Root et al ( 91 ) identified that Dmp1‐creER ‐labeled perivascular osteoprogenitors localized in the trans‐cortical channel are mobilized by PTH treatment and increase mature osteoblasts. These results indicate that the diverse origins of osteoblasts contribute to the PTH‐induced bone anabolic actions.…”
Section: The Origin Of Osteoblasts In Bone Anabolismmentioning
confidence: 99%
“…Initially, augmentation procedures often involved the use of autologous bone obtained from the same patient, either alone or combined with bone substitutes to subsequently allow the placement of dental implants [ 2 ]. Autologous bone is a favorable graft because of its osteoconductive properties [ 3 ], osteogenic activity [ 4 , 5 ], and source of growth factors stored in the matrix [ 6 ]. However, the limited amount of local autologous bone and the morbidity upon harvesting [ 7 ] has stimulated the search for alternative sources of these bone substitutes including allografts and xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible, therefore, that vascular smooth muscle cells may still have some potential for trans-differentiation [16,18,20]. Bone arteries are in fact reportedly covered with SMA-positive cells that have the potential to differentiate into one of many mesenchymal lineages including osteoblasts [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%